Increasing Role of Ports in Global Trends of logistics Network Restructuring-“An Organizational Study of Cochin Port Trust” - Dr G.K.Mittal (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Seaborne trade continues to expand, bringing benefits for consumer across the world through low and decreasing freight costs. Port plays a key role in the growth of seaborne trade. Without ports the entire region would remain underdeveloped and dormant. A port is a location on a coast or shore containing one or more harbors where ships can dock and transfer people or cargo to or from land. Since ports throughout history handled every kind of traffic, supports facilities vary widely, may extend for miles and dominates the local economy.Cochin Port is a major port on the Arabian Sea and Indian Ocean sea route and is one of the largest ports in India. Cochin Port